(untitled) (International Conference on Computers in Education, 2013)
Previous studies show that storytelling is a powerful approach in EFL (English as Foreign Language) elementary classroom because it can facilitate young EFL students to engage in acquisition, provide a rich source of materials, and open communication and interaction possibilities by telling their own stories. In recent years, digital storytelling in a classroom further provides a strategy for teachers to effectively move beyond the print-based texts and engage students in working with digital multimodal texts. Digital storytelling requires students to bring together various modes such as written words, images, and sounds into their own multimodal representations. Recently, many forms of electronic books such as tablet PCs have become available to facilitate English learning and may be applied to implement storytelling activities. Although theories and research support the significance and education value of using digital storytelling, however, empirical studies of using digital storytelling in EFL elementary context is scant because teachers are often overwhelmed by difficulties such as students’ English limited English proficiency, teacher’s pressure of existed curriculum and the lacking pedagogy of using digital storytelling. This study develops digital storytelling pedagogy with iPads to overcome the difficulties and conducts a five-month quasi-experimental study to determine whether digital storytelling pedagogy has the intended effect on participants’ motivation and achievement. Two intact classes (N=32) were randomly assigned as the digital storytelling group and traditional teacher-centered group. Participants’ achievement will be discussed.